2019
DOI: 10.1556/2006.7.2018.133
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective and prospective assessments of gambling-related behaviors across the female menstrual cycle

Abstract: Background and aims: Despite increases in female gambling, little research investigates female-specific factors affecting gambling behavior (GB). Although research suggests that some addictive behaviors may fluctuate across menstrual cycle phase (MCP), gambling requires further investigation. In two studies, we examined associations between MCP and three risky GBs: time spent gambling, money spent gambling, and the probability of consuming alcohol while gambling. Associations between MCP and negative affect we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…Another example of GD as self-medication derives from the relationship between premenstrual symptoms and the associated perimenopausal depression in women ( 90 ). Women are at increased risk for gambling-related behaviors before and during menstruation (in comparison with other phases of the menstrual cycle) which may be a means of self-medication for the elevated negative affect ( 91 ).…”
Section: Etiopathogenesis Of Gambling Dual Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of GD as self-medication derives from the relationship between premenstrual symptoms and the associated perimenopausal depression in women ( 90 ). Women are at increased risk for gambling-related behaviors before and during menstruation (in comparison with other phases of the menstrual cycle) which may be a means of self-medication for the elevated negative affect ( 91 ).…”
Section: Etiopathogenesis Of Gambling Dual Disordermentioning
confidence: 99%
“…Investigations suggest that some addictive behaviors (including GD) can fluctuate over the menstrual cycle. Indeed, a recent study found that gambling behaviors (time spent gambling, money spent on gambling, and the probability of consuming alcohol while gambling) are exacerbated during ovulation ( 91 ).…”
Section: Etiopathogenesis Of Gambling Dual Disordermentioning
confidence: 99%
“…First, we tested only male participants, who tend to show higher levels of risk-taking (Cross et al 2011) and higher rates of problem gambling (Kessler et al 2008), but generalization to females cannot be assumed. Rates of problem gambling appear to be increasing among females (McCarthy et al 2019), and gambling tendencies (including the use of alcohol while gambling) were recently linked to menstrual cycle phase (Joyce et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Further, because our scoping review focuses on the emergence of a new methodology, and our goal is to demonstrate applications and help delineate future research questions to move this small literature forward, we found this number sufficient for this goal. One of the nine records we selected (Joyce et al, 2019 ) described two different studies. We coded only the second study they presented as the first study did not satisfy inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%